Experiences as an AmeriCorps Nutrition Educator for Harvesters--The Community Food Network - Louk, Julie (My University, 2012)
Nearly fifteen percent of households in the United States experienced food insecurity in 2008 and 2009 (one-third of which experienced low food security). Malnourishment resulting from food insecurity may lead to developmental disorders and learning difficulties in addition to other poor health outcomes. In the United States, obesity and its related morbidities such as cardiovascular disease and diabetes account for a portion of these poor health outcomes. Harvesters—The Community Food Network strives to end food insecurity throughout northwestern Missouri and northeastern Kansas through the implementation of four feeding and hunger initiatives. The Nutrition Services Department at Harvesters contributes to two of the initiatives by providing nutrition education to youth and adults in order to facilitate behavior changes which lead to a healthier lifestyle, thereby reducing the prevalence of negative health outcomes among the population served by Harvesters. The present report contains details regarding a field experience as an AmeriCorps Nutrition Education Specialist for Harvesters. During the experience, the student produced a four week curriculum designed to increase children’s awareness about the importance of eating a variety of fruits and vegetables; the lesson further provided the opportunity for children to sample fruits and vegetables prepared in recipes selected for children’s enjoyment. The majority of the student’s time was spent educating children, teens and adults about nutrition and cooking; the student accrued 974 participant visits by facilitating 73 class sessions.
Keywords: AmeriCorps; Harvesters; Food insecurity; Obesity; Food Banking System; Public Health (0573)